CONTRACTOR SALES ACCOUNTING SYSTEM AT CV. XYZ IN CIKARANG - Mutansir (JACTA: Journal of Accounting and Tax, 2022)
This final project entitle “Accounting System Sales Contractor Services on CV Arjuna Karya Mandiri in Cikarang. The purpose of this study was to determine the Accounting System Sales Contractor Services at CV. Arjuna Karya Mandiri, to find out the Accounting recording system, Knowing the relate parts in the sale of service, Knowing the Internal control system in the Contractor Sales Accounting System at CV. Arjuna Karya Mandiri. This study uses a descriptive method based on qualitative data wichh is used to explain the accounting System for Contractor Service Sales. The technique of collecting data in this research is by means library research and field studies. Based on the discussion, it can be concluded that the Service Sales Accounting System in CV. Arjuna Karya Mandiri has relate sections, namely General & Administration Division, Palnning Technicak Devision and Finansial Controller. The document used are Billing Laters, Receipts Service and journal entries generally using the MYOB application. Internal control is still not good because it has not separated the accounting function and the cash function.